Providing Legal Consultation (Non Judicial) Regarding Inherited Land to Justiabelen - Rolib Sitorus; Alum Simbolon; Sryani Br. Ginting; Ricky Banke; Christina N.M. Tobing (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
The tridharma of higher education includes education and teaching, research and community service is the pulse in the implementation of higher education in Indonesia. The Law Study Program at Pelita Harapan University (UPH) Medan Campus as a higher education unit carries out the Tridharma of Higher Education based on the provisions outlined by the government.The Law Study Program organizes community service activities through the Legal Consultation and Aid Institute (LKBH) which was established based on the Decree of the UPH Chancellor. LKBH provides consultation and legal assistance to people seeking justice so that their rights are not neglected, especially to ordinary people who are legal and economically disadvantaged. LKBH plays a role in helping the community through consultation and legal assistance is provided free of charge.Community service activities are non-judicial legal consultations with Mrs. Ida Darli Purba justiabelen related to inherited land. This land dispute issue is related to land ownership that does not yet have a land title certificate. In this activity, the inheritance land with the right of title in the form of a Camat Decree is not controlled and there are no buildings and is not cultivated/used for business activities by the mother-in-law of Ida Darli Purba, as well as the family concerned until now. To resolve this problem, proper and correct data is needed, so that the rights to the disputed land can be registered and the land certificate becomes legal certainty of the related land ownership.